A saúde mental na atenção básica: um diálogo necessário - Marilia Rezende da Silveira (2009)
This work aims to study caring strategies for mental health patients in the healthservice of the Health District in Pampulha neighborhood (DISAP), in the city of BeloHorizonte, M.G. It discusses the users insertion in this health network through theanalysis of articulation/integration ways of the Mental Health actions in basicattention, taking the patterns proposed in the Psychiatric Reform as the starting point.It identifies strategies to introduce therapeutic actions in basic attention which canguarantee the patients reinsertion when back to their environment. It is a qualitativework based on the theoretical-methodological aspect of the dialectic-historicmaterialism. It considers that its purposes allow one to face the present reality incultural and social-historical relations in the present development and the changes inthe psychiatric assistance pattern to try to understand this reality through this focus.In this context Mental Health policy is the result of formulation and reformulation,each close look revealing contradictions and subsequent changes in assistancepractice, as well as knowing how to deal with insanity. Two analytical categoriesmarked the research accomplishment in all its phases: professionals practice ofthose who assist mental health patients and this subjects social reinsertion. Thisstudy took place at DISAP, which is in favor of the proposals commended in thePsychiatric Reform. There were 25 interviews with professionals at the HealthService and two focal groups with the patients. In order to build the empiricalcategories the speech analysis technique has been used to gather topicsinterviewees argued about. Some topics enabled the recognition of three empiricalcategories: a) the assistance pattern in mental health: a project and its difficulties;b) Mental Health and Basic Attention: the needed team articulation in caring work,aspects which were highlighted in two subcategories: caring work impasses andovercoming strategies and matrix support co-responsibilities and co-participation;and c) psychosocial reinsertion, a complex process which demands constant dealsinvolving the family and the institutions for material and emotional exchanges thatcan put the patients back to their environment. In this process the symptom is takeninto account as the way patients can transmit to others the meaning of their suffering.Due to the aspects, dimensions and complexities of the topic of this study, looking forstrategies in government organizations and in society to create new socialorganization ways is imperative to guarantee the success of the Psychiatric Reform.